The Effect Of Service Quality And Marketing Mix On Customer Loyalty Outsourcing Security PT. Tri Garda Abbas East Jakarta - Yulianti, Lusi; Fa’uzobihi, Fa’uzobihi; Taryanto, Taryanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to determine the effect of service quality on customer loyalty marketing mix towards customer loyalty and know the quality of shared services marketing mix on customer loyalty Outsourcing security PT. Tri Garda Abbas, East Jakarta. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. This research uses the method of purposive sampling saturated used amount 97 employee PT. Tri Garda Abbas, East Jakarta, using multiple linear regression data analysis techniques. The results of this research show that there is an influence of service quality on customer loyalty marketing mix on customer loyalty, and there is an influence on service quality and marketing mix simultaneously or together on customer loyalty Outsourcing security PT. Tri Garda Abbas, East Jakarta, has an influential contribution of 33,5% on the customer loyalty variable. It is hoped that the results of this research will contribute to further research